2010
DOI: 10.1677/joe-10-0104
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal nicotine exposure causes insulin and leptin resistance and inhibits hypothalamic leptin signaling in adult rat offspring

Abstract: Maternal nicotine (NIC) exposure during lactation leads to overweight, hyperleptinemia, and hypothyroidism in adult rat offspring. In this model, we analyzed adipocyte morphology, glucose homeostasis (serum insulin and adiponectin; liver and muscle glycogen), serum lipid, and the leptin signaling pathway. After birth, osmotic minipumps were implanted in lactating rats, which were divided into the groups NIC (6 mg/kg per day s.c. for 14 days) and control (C, saline). NIC and C offspring were killed at the age o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
53
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 43 publications
7
53
0
Order By: Relevance
“…The pumps were prepared with nicotinefree base diluted in a saline solution (NaCl 0.9%) and set to deliver an initial dose of 6 mg/kg of nicotine per day for 14 days of lactation. Cotinine milk and serum concentrations had already been determined in this experimental model (de Oliveira et al 2010. The chosen dose in our study produces plasma nicotine levels of approximately 25 ng/ml, which are similar to those observed in typical smokers (Lichtensteiger et al 1988).…”
Section: Model Of Postnatal Nicotine Exposuresupporting
confidence: 77%
See 1 more Smart Citation
“…The pumps were prepared with nicotinefree base diluted in a saline solution (NaCl 0.9%) and set to deliver an initial dose of 6 mg/kg of nicotine per day for 14 days of lactation. Cotinine milk and serum concentrations had already been determined in this experimental model (de Oliveira et al 2010. The chosen dose in our study produces plasma nicotine levels of approximately 25 ng/ml, which are similar to those observed in typical smokers (Lichtensteiger et al 1988).…”
Section: Model Of Postnatal Nicotine Exposuresupporting
confidence: 77%
“…In adulthood, they were programed for overweight, secondary hypothyroidism (lower TSH, T 4 , and T 3 levels), and hyperleptinemia ). We also showed leptin and insulin resistance (de Oliveira et al 2010), increased medullary adrenal function and serum glucocorticoid levels with higher levels of corticotropin-releasing hormone (CRH) and adrenocorticotropic hormone (ACTH) in adult offspring whose mothers were nicotine-exposed .…”
mentioning
confidence: 89%
“…Surprisingly, when adults, these offspring were programmed only for adrenal dysfunction, characterized by decreased total adrenal catecholamine content and tyrosine hydroxylase protein expression (Santos-Silva et al 2012). These findings were different from those obtained from the maternal nicotine model (Oliveira et al 2009, de Oliveira et al 2010, suggesting that the combination of nicotine and other cigarette components programs for different outcomes than the maternal nicotine model. Actually, children from smoking mothers are exposed to cigarette components not only through breast milk but also through the household environment.…”
Section: Introductionmentioning
confidence: 82%
“…Nicotine is transferred by breast milk and promotes, in pups, higher body fat mass with metabolic alterations featured by hyperleptinemia, primary thyroid hypofunction, and higher adrenal catecholamine content and corticosterone levels (Oliveira et al 2009. In adult life, it programs the progeny for overweight and higher adiposity associated with leptin and insulin resistance as well as secondary hypothyroidism with alterations in the leptin signaling pathway of hypothalamus-pituitary-thyroid axis (Oliveira et al 2009, de Oliveira et al 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal nicotine exposure restricted to the lactating period also leads to early and late metabolic defects. Higher levels of HDL-C, leptin, corticosterone and adrenal catecholamine content are observed at PND15, ) and overweight (with increased fat mass and hypertrophy of adipocyte), hyperleptinemia (with impaired hypothalamic leptin signaling), hyperinsulinemia and hypothyroidism are reported in adult rat offspring exposed to nicotine through maternal milk (de Oliveira et al 2010). Different mechanisms could explain the enhanced adipose storage due to early nicotine exposure during the early stage of development such as (1) increased release and transport of fatty acids from maternal adipose tissue to the fetal circulation (Williams and Kanagasabai 1984), (2) a nicotine-mediated stimulatory effect on PPAR-c gene expression in the adipocyte (Somm et al 2008), as previously observed in monocytes (Amoruso Table 2).…”
Section: Early Deleterious Programming Actionmentioning
confidence: 99%